Readiness for hospital discharge perceived by caregivers of patients with traumatic brain injury: A cross-sectional study - Ganefianty, Amelia; Songwathana, Praneed; Damkliang, Jintana (Belitung Nursing Journal, 2024)
Background: There is a growing emphasis on evaluating discharge readiness, particularly for those involved in the care of patients in transition. Caregivers supporting individuals with traumatic brain injury are a specific focus due to the potential impact of adequate discharge preparation on patient recovery and post-discharge outcomes. Objective: This research aimed to evaluate the preparedness of caregivers for the discharge of patients with moderate or severe traumatic brain injury from the hospital. Methods: This cross-sectional study was carried out in a tertiary hospital in Indonesia from January to April 2023 using the Indonesian adaptation of the Preparedness for Caregiving Scale. The study comprised seventy-four caregivers of individuals with traumatic brain injury, chosen through a purposive sampling approach based on pre-established inclusion and exclusion criteria. Data collection involved a questionnaire covering caregiver information (gender, age, education level, income, and psychological status) and discharge readiness. Descriptive statistics and correlation analyses, employing Pearson and chi-square, were conducted. Results: Most caregivers were female (83.8%), spouses of patients (50%), and had a moderate education level (52.7%). The average age of caregivers was 43.7 ± 8.7 years, with an average duration of patient care of 4.22 ± 1.2 days and a monthly income of 220 US dollars. The mean score for readiness for hospital discharge was low (10.08 ± 1.91), indicating that caregivers were not adequately prepared for discharge. Age and education were significant factors (p <0.05) related to hospital discharge readiness. Conclusion: This study emphasizes the importance of assessing caregiver readiness for the discharge of patients with traumatic brain injury from the hospital. Findings indicate a concerning trend of inadequate preparedness among caregivers, with factors such as age and education level significantly influencing readiness. The predominance of female caregivers, often spouses of patients, indicates the need for tailored support strategies. Prioritizing caregiver preparation and support, especially by nurses, is crucial for optimizing patient recovery and post-discharge outcomes.